The American Jewish Story through Cinema - Goldman, Eric A. (Book collections on Project MUSE., 2013)
By analyzing select mainstream films from the beginning of the sound era up through the early twenty-first century, this study uses the medium of cinema to provide an understanding of the American Jewish experience over the last century.